2019
DOI: 10.1785/0120190071
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Amplification and Attenuation Effects in the Atlantic and Gulf Coastal Plain Using Spectral Ratios

Abstract: The Atlantic and Gulf Coastal Plain in the southern and southeastern United States contains extensive Cretaceous and Cenozoic sedimentary sequences of variable thickness. We investigated the difference in response of sites in the Coastal Plain relative to sites outside that region using Fourier spectral ratios from 17 regional earthquakes occurring in 2010–2018 recorded by the Earthscope transportable array and other stations. We used mean coda and Lg spectra for sites outside the Coastal Plain as a reference.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…We used mean coda and Lg spectra for sites outside the Coastal Plain as a reference. We found that Coastal Plain sites experience amplification of low-frequency ground motions and attenuation at high-frequencies relative to average site conditions outside the Coastal Plain (Guo and Chapman, 2019). The spectral ratios at high frequencies gave estimates of the difference between kappa, a measure of ground motion attenuation, at Coastal Plain sites and the reference condition.…”
Section: By Martin C Chapman (Virginia Polytechnic Institute and Stat...mentioning
confidence: 88%
See 2 more Smart Citations
“…We used mean coda and Lg spectra for sites outside the Coastal Plain as a reference. We found that Coastal Plain sites experience amplification of low-frequency ground motions and attenuation at high-frequencies relative to average site conditions outside the Coastal Plain (Guo and Chapman, 2019). The spectral ratios at high frequencies gave estimates of the difference between kappa, a measure of ground motion attenuation, at Coastal Plain sites and the reference condition.…”
Section: By Martin C Chapman (Virginia Polytechnic Institute and Stat...mentioning
confidence: 88%
“…By Oliver S. Boyd (USGS) and Sarah Mills (Colorado School of Mines) Earthquake ground motions along the Atlantic and Gulf Coastal Plains show significant frequency-dependent deviations relative to other areas in the Central and Eastern United States (Guo and Chapman, 2019;Pratt and Schleicher, 2021). Ground motions have been shown to be strongly correlated with sediment thickness, where sediment is generally defined as being of Cretaceous Period or younger age.…”
Section: "Sediment Thickness Along the Atlantic And Gulf Coastal Plains"mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of regional CENA attenuation models are numerous; recent works include Cramer (2017), Cramer and Al Noman (2016), Bisrat et al (2014), Yassminh et al (2020), Chapman and Conn (2016), Guo and Chapman (2019), Pasyanos (2013), Gallegos et al (2014), and NGA-East (PEER, 2015). The NGA-East project was a multi-disciplinary research project managed by Christine Goulet with the objective to develop a new ground motion characterization (GMC) model for CENA.…”
Section: Introductionmentioning
confidence: 99%
“…Guo and Chapman (2019) evaluated the difference between site response inside and outside of the Coastal Plain (Atlantic and Gulf) using Lg-wave spectral ratios and assuming an average Q common to all stations and sources. This method incorporates any variations in crustal attenuation into the site term which is based on sediment thickness in the coastal plains.…”
Section: Introductionmentioning
confidence: 99%